2014
DOI: 10.1063/1.4860555
|View full text |Cite
|
Sign up to set email alerts
|

Solid phases of spatially nanoconfined oxygen: A neutron scattering study

Abstract: We present a comprehensive neutron scattering study on solid oxygen spatially confined in 12 nm wide alumina nanochannels. Elastic scattering experiments reveal a structural phase sequence known from bulk oxygen. With decreasing temperature cubic γ-, orthorhombic β- and monoclinic α-phases are unambiguously identified in confinement. Weak antiferromagnetic ordering is observed in the confined monoclinic α-phase. Rocking scans reveal that oxygen nanocrystals inside the tubular channels do not form an isotropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Preferred orientations compatible with this selection mechanism for the crystalline orientations have been reported for other simple building blocks confined in nanoporous templates, e.g. for argon [107,117], nitrogen [117,192], oxygen [201,184], other medium length n-alkanes [193,202], n-alcohols [203,204], and for the smectic state of liquid crystals [205,206].…”
Section: Liquid-solid Transition Crystallisation and Texture Formationsupporting
confidence: 54%
See 1 more Smart Citation
“…Preferred orientations compatible with this selection mechanism for the crystalline orientations have been reported for other simple building blocks confined in nanoporous templates, e.g. for argon [107,117], nitrogen [117,192], oxygen [201,184], other medium length n-alkanes [193,202], n-alcohols [203,204], and for the smectic state of liquid crystals [205,206].…”
Section: Liquid-solid Transition Crystallisation and Texture Formationsupporting
confidence: 54%
“…Hofmann et al [184] showed in a recent neutron diffraction study that the oxygen nanocrystals inside tubular alumina of 12 nm channels do not form an isotropic powder. Rather, they exhibit preferred orientations sensitively depending on the thermal history.…”
Section: Structural Solid-solid Phase Transformationsmentioning
confidence: 99%
“…Besides, oxygen possesses three further phases for pressures in the range of several GPa . A great number of papers, which applied different techniques (in particular diffraction, scattering, and optical transmission), have addressed the influence of confinement on the behavior of oxygen and partly report of deviations in comparison to bulk oxygen. First, the transition temperature from liquid to solid and the melting temperature differ and both are shifted to lower temperatures. ,, The magnitude of the temperature shift in comparison to the transition temperature of bulk oxygen is inversely proportional to the pore radius r P , an observation which has also been made for a multitude of other substances. , Second, the solid–solid phase transitions are similarly shifted to lower temperatures and exhibit a hysteresis. ,,, Furthermore, for some nanoporous materials (silica xerogels, SBA-15) the absence of the transition from β- to α-oxygen was reported. , On the other hand, for other porous silica the existence of a phase resembling the structure of α-oxygen was reported (for r P ≳ 3.8 nm), and for porous aluminum ( r P = 6 nm) the α-phase was detected using neutron scattering . The formation of the crystalline structures of solid oxygen depends in particular on the pore size and the filling of the pores and also a mixing of different crystal phases was observed. ,,,, In small nanpores ( r P ≈ 1.8 nm), e.g., only an amorphous structure of the oxygen molecules was found at low temperatures and for incomplete fillings of nanopores ( r P = 5.3 nm) a partial or even complete suppression of the γ–β-transition was reported .…”
Section: Introductionmentioning
confidence: 92%
“…Solid oxygen exhibits different phases both in bulk and in confinement. At its vapor pressure oxygen transforms during cooling from the liquid phase to the so-called γ-phase (at T = 54.36 K), to the β-phase (at T = 43.80 K), and finally to the α-phase (at T = 23.88 K) . These phases differ regarding the ordering and arrangement of the molecules, which also influence the magnetic properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation